Labour and the Irish party system revisited - party competition in the 1920s - Mair, Peter (Economic & Social Studies, 1977)
In the 1969 General Election the Labour Party received more votes than at any other time in its electoral history. Nevertheless, despite this success, Labour continues to be one of the smallest social democratic parties in contemporary Europe. While many different reasons have been advanced to explain Labour's persistent weakness, there is general acceptance that the party's low level of electoral strength can be related both to the traditionally small industrial sector in Ireland ? and so to the absence of significant working-class population ? and to the apparently impregnable dominance of a nationalist political cleavage which has resolutely discouraged the emergence of an influential capital-labour opposition. In this sense, Labour's weakness can be seen in terms of its inability to compete with the larger parties which have organised their support in terms of variations on a nationalist/republican theme, and which have effectively rendered irrelevant the Labour demand that the electorate mobilise around strictly social and economic issues.
Keywords: Party politics - Ireland; Labour Party - Ireland